2022
DOI: 10.32615/ps.2022.019
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the mitochondrial alternative oxidase pathway improves PSII function and photosynthetic electron transport in tomato seedlings under chilling stress

Abstract: Abbreviations: CEF-PSI -cyclic electron transport around PSI; ETR -electron transport rate; F0 -minimal fluorescence yield of the dark-adapted state; Fm -maximal fluorescence yield of the dark-adapted state; Fv/Fm -maximal quantum yield of PSII photochemistry; NPQ -nonphotochemical quenching; OEC -oxygen-evolving complex; OJIP curve -Chl a fluorescence transient; PIABS -performance index for energy conservation from photons absorbed by PSII until the reduction of intersystem electron acceptors; Pm -maximum P70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…From the L-band and K-band, we can understand the group of the PSII subunits or energetic connectivity between the antenna and RCs of PSII and the situation of OEC centers at the PSII donor side ( Strasser et al., 2004 ; Kalaji et al., 2018 ). Studies showed that the K-band usually occurred in plants that suffer from chilling, heat or drought stress ( Strasser et al., 2004 ; Chen et al., 2016 ; Silva Dalberto et al., 2017 ; Dimitrova et al., 2020 ; Zeng et al., 2022 ). This phenomenon might be indirectly caused by the block of PSII electron flow beyond Q A , resulting in a large accumulation of reactive oxygen species (ROS) in PSII ( Rutherford and Krieger-Liszkay, 2001 ; Guo et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…From the L-band and K-band, we can understand the group of the PSII subunits or energetic connectivity between the antenna and RCs of PSII and the situation of OEC centers at the PSII donor side ( Strasser et al., 2004 ; Kalaji et al., 2018 ). Studies showed that the K-band usually occurred in plants that suffer from chilling, heat or drought stress ( Strasser et al., 2004 ; Chen et al., 2016 ; Silva Dalberto et al., 2017 ; Dimitrova et al., 2020 ; Zeng et al., 2022 ). This phenomenon might be indirectly caused by the block of PSII electron flow beyond Q A , resulting in a large accumulation of reactive oxygen species (ROS) in PSII ( Rutherford and Krieger-Liszkay, 2001 ; Guo et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that PSII is a thermolabile component of thylakoid membranes, susceptible to heat stress (Havaux and Tardy, 1996; Hu et al, 2020; Wang et al, 2022). Heat stress impedes not only the oxygen‐evolving complex of PSII (Enami et al, 1994) but also adversely affects Fv/Fm , ATP synthesis, and electron transport of PSII (Ahammed et al, 2018; Zeng et al, 2022; Lü et al, 2023; Havaux, 1993). Our findings indicate that the heat stress diminished the Pn , Fv/Fm , ETR, and quantum yields of PSII in all genotypes examined.…”
Section: Discussionmentioning
confidence: 99%